AKHULGO: ON THE ISSUE OF THE FAILED “PEACE NEGOTIATIONS” ACCORDING TO LOCAL CHRONICLES AND OFFICIAL RUSSIAN SOURCES (JUNE-AUGUST OF 1839) - Tahnaeva, Patimat Ibragimovna (History, Archeology and Ethnography of the Caucasus, 2020)
The Battle for Akhulgo was one the largest military operations of the Caucasian War, carried out in Dagestan by the Chechen detachment of the Caucasian army under the command of Lieutenant General P.H. Grabbe from June, 12 to August, 29, 1839. It is known that the parties made numerous attempts to end this bloody confrontation by negotiations: according to Russian sources – the negotiations on surrender, according to local ones – on peace agreement. The paper presents the points of view of the both parties, dynamics and subject of the negotiating process, its connection to different stages of the siege. The author introduces a new source, an official document, a detailed chronicle of the siege of Akhulgo – military journals of the detachment from June 12 to August 30, 1839, which was filled daily by the commander of the expeditionary detachment Lieutenant General P.H. Grabbe. The negotiations, which were carried out in the second half of August, according to local and Russian sources, ended ambiguously – with the release of the imam’s son as a hostage (“amanate”) and the siege of Akhulgo. The parties accused each other of violating their obligations or failure to fulfill them. According to official Russian sources, the solution of the tasks of “suppressing Dagestan” in 1839, set by Emperor Nicholas I before the Caucasian command, implied “the destruction of the fortified home of Shamil on the Akhulgo Rock” and “the elimination of Shamil”. The ultimate goal of solving these problems excluded the conclusion of peace agreements with the mountaineers. Nevertheless, according to local sources (Muhammad-Tahir al-Karakhi, Abdurahman al-Gazigumuki, Haji Ali, H. Genichutlinsky) the "failed peace talks" were remembered as a story of "deception and break of the Russian promises".